Demographic profile of an overexploited serranid, the orange-spotted grouper (Epinephelus coioides), from Northern Oman - McIlwain, Jennifer; Ambu-Ali, A.; Al Jardani, N.; Halford, A.; Al-Oufi, H.; Feary, D. (U.S. National Marine Fisheries Service, 2016)
Age, growth, and monthly reproductive characteristics were determined for the orange-spotted grouper (Epinephelus coioides) from northern Oman. This species is characterized by a prevalence of females (1-11 years old), and males make up 6.5% of the total sample. Growth parameters indicate a typical pattern for groupers with a low growth coefficient (K=0.135). The trajectory of the von Bertalanffy growth function was almost linear with no evidence of asymptotic growth. Estimates of mortality revealed a low natural mortality of 0.14/year but a high fishing mortality of 0.59/year. More alarming was the high rate of exploitation (0.81/year), considered unsustainable for a slow-growing grouper. The population off southern Oman is diandric protogynous, and sex change takes place between 449 and 748 mm in total length (TL) or over a period of 4–8 years. The gonadosomatic index for females showed a short spawning season from March through May, although ~30% of females were ripe for 7 months of the year. Size and age at 50% maturity for females was estimated to be 580 mm TL and 4 years, respectively. We suggest that substantial changes in the management of this species will be vital in sustaining viable populations of orange-spotted grouper and other species of Epinephelidae within Oman.